Learning English at home: Exploring Indonesian EFL students’ online learning experiences during the Covid-19 Pandemic - Dairabi Kamil (Edukasi, 2022)
This study seeks to, first, explore Indonesian EFL students’ experiences in online learning during Covid-19 Pandemic; second, reveal how the online learning impacted on their learning of the four language skills; and third, enlist their preferred modes of learning in the aftermath of the pandemic. Drawing on a qualitative design and phenomenological approach, the data were collected through online interviews with purposely selected 12 English department students of a state Islamic university in Indonesia and analyzed using Thematic Analysis technique. The findings showed that the majority of the students had unpleasant experiences in online learning due to internet access problems, lack of interaction, stress and demotivation, and difficulty in understanding the lesson. The online learning provided more opportunities for them to develop their reading, listening, and writing skills but significantly reduced the space for practicing speaking. Most of the students preferred going back face-to-face classroom learning in the aftermath of the pandemic. Few preferred a combination of offline and online learning. Nevertheless, they acknowledged that online learning trained them to be a more independent learner, raised awareness of the use of technology for language learning, and offered a mode learning that was flexible, handy, rich of sources, and selectable to their learning needs.